A New Management Strategy for Hemimasticatory Spasm - Zhang, Zhongding; Lu, Datan; Ying, Tingting; Li, Shiting; Zhao, Hua (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2025)
Background Hemimasticatory spasm (HMS) is an uncommon movement disorder of the trigeminal motor rootlet characterized by unilateral, involuntary, and paroxysmal contractions of the muscles of mastication. The mechanisms for HMS are still unclear, and an efficient treatment strategy still needs to be developed. This study aims to investigate the clinical features and surgical treatment of HMS.Methods Twelve patients with HMS were included in our study. The patient data regarding clinical characteristics, neuroimaging presentations, intraoperative findings, and treatment outcomes were analyzed retrospectively. Highly selective trigeminal motor root rhizotomy (HSTR) combined with microvascular compression was performed in nine cases with neurovascular conflict, whereas three patients without vascular compression underwent HSTR only.Results Intraoperative findings showed that there were two patients with six branches, two patients with five branches, and the remaining patients with three to four branches of the trigeminal motor roots. Seven patients had two motor branches severed, three patients had one motor branch severed, and two patients each had three motor branches severed. Nine patients recovered uneventfully and showed no signs of spasms, and the remaining two patients experienced complete disappearance of symptoms within 3 months after surgery. In one patient, the symptoms disappeared immediately after surgery but recurred 2 years later.Conclusion The surgical procedures of HSTR can significantly alleviate the clinical symptoms of patients with HMS without serious complications.
Keywords: hemimasticatory spasm; rhizotomy; microvascular compression